KONDISI BATAS MEDIUM PADA KOMPUTASI PENJALARAN GELOMBANG ELASTIK 2D MENGGUNAKAN METODE BEDA HINGGA - Antonius Alex Harmoko (PPSDM Geominerba, 2019)
In seismic wave propagation modeling, the problem is the boundary conditions of the model to approach the real situation. The boundary conditions of the model are edges, free surfaces, and boundaries between layers. In this study, 2D elastic wave propagation simulation was made using a fourth order finite difference approach and staggered grid by applying boundary conditions to the modeling. At the edges of the model, the pseudo boundary conditions were applied using the damping function to eliminate the effect of reflection on the edges of the medium model. On the free surface, the boundary conditions of the free surface are applied where the stress on the surface is zero and in the boundary between layers, all stresses and shift vectors are continuous so that propagation at the boundary of the medium will be correct. The wave source used is a Gaussian derivative. By varying the use of damping factor (Df) and damping width (nabs) at the edge of the medium model, the optimum attenuation for the pseudo boundary conditions of the model is at Df= 3 and n abs at 70-100 grid points. Free surface and between layers boundary condition are used to make corrections to the wave propagation phase changes when a wave hits the model boundary.